Structural Simulation of Wheelchair Ramp using Finite Element Method - Lenggana, Bhre Wangsa; Nugroho, Agung; Ubaidillah, Ubaidillah (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Wheelchairs are essential mobility aids for people with disabilities, but they are often limited to flat surfaces and cannot overcome height differences. Portable ramps are an effective solution to overcome this limitation. This research aims to simulate and analyze the structure of a portable ramp for wheelchairs. Simulations were conducted using finite element method analysis software to assess the portable ramp's von Mises stress, deformation, and safety factor in various loading positions. Finite element method (FEM) analysis software was utilized to evaluate key mechanical properties, including von Mises stress, deformation, and safety factor, under different loading conditions and positions. The simulation results demonstrated that the proposed portable ramp design can safely endure various load placements without exceeding the material's stress limits. The von Mises stress, deformation, and safety factors remained within acceptable ranges, validating the ramp's structural integrity and safety. Based on the initial findings, design modifications were implemented to further enhance the ramp's strength, durability, and user safety. This research not only confirms the effectiveness of the proposed ramp but also suggests improvements to optimize its performance. The final portable ramp design offers a reliable, cost-effective, and market-competitive solution that can significantly improve the mobility and independence of wheelchair users, enabling them to navigate a broader range of environments and overcome everyday obstacles with greater ease and confidence.